2019
DOI: 10.1097/md.0000000000016549
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intravascular and surface cooling devices for targeted temperature management after out-of-hospital cardiac arrest

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In a retrospective observational study using a nationwide OHCA database in Korea, propensity score matching was used to compare intravascular and surface cooling devices. 61 While no difference was found in survival to hospital discharge or good neurologic outcome between patients treated with surface or intravascular cooling, in a subgroup of patients >65 years old, IVTM was associated with good neurologic outcomes (OR 3.97 [1.19-13.23], P = .02). 61 In a systematic review and meta-analysis of 12 studies, which included 5581 patients treated with temperature control (28% IVTM and 72% surface cooling), IVTM was associated with improved neurologic outcomes (pooled risk difference 5% [95% CI 2%, 8%]), lower risk of arrhythmia (pooled risk difference 6% [95% CI 2%, 11%]), and lower risk of overcooling (pooled difference 15% [95% CI 7%, 22%]) compared to surface cooling.…”
Section: Components Of High-quality Temperature Controlmentioning
confidence: 83%
See 1 more Smart Citation
“…In a retrospective observational study using a nationwide OHCA database in Korea, propensity score matching was used to compare intravascular and surface cooling devices. 61 While no difference was found in survival to hospital discharge or good neurologic outcome between patients treated with surface or intravascular cooling, in a subgroup of patients >65 years old, IVTM was associated with good neurologic outcomes (OR 3.97 [1.19-13.23], P = .02). 61 In a systematic review and meta-analysis of 12 studies, which included 5581 patients treated with temperature control (28% IVTM and 72% surface cooling), IVTM was associated with improved neurologic outcomes (pooled risk difference 5% [95% CI 2%, 8%]), lower risk of arrhythmia (pooled risk difference 6% [95% CI 2%, 11%]), and lower risk of overcooling (pooled difference 15% [95% CI 7%, 22%]) compared to surface cooling.…”
Section: Components Of High-quality Temperature Controlmentioning
confidence: 83%
“…61 While no difference was found in survival to hospital discharge or good neurologic outcome between patients treated with surface or intravascular cooling, in a subgroup of patients >65 years old, IVTM was associated with good neurologic outcomes (OR 3.97 [1.19-13.23], P = .02). 61 In a systematic review and meta-analysis of 12 studies, which included 5581 patients treated with temperature control (28% IVTM and 72% surface cooling), IVTM was associated with improved neurologic outcomes (pooled risk difference 5% [95% CI 2%, 8%]), lower risk of arrhythmia (pooled risk difference 6% [95% CI 2%, 11%]), and lower risk of overcooling (pooled difference 15% [95% CI 7%, 22%]) compared to surface cooling. 62 In another systematic review and meta-analysis, which only included randomized controlled trials, all modes of temperature control were superior to no temperature control; among cooling modes, IVTM was superior to surface cooling (ranking p-score 0.960 vs 0.670).…”
Section: Components Of High-quality Temperature Controlmentioning
confidence: 83%
“…Of these, 30 further studies (one RCT [19] and 29 non-RCTs) were excluded after the full-text screening. Three non-RCTs were partially using the same data from the Korean Centers for Disease Control and Prevention out-of-hospital cardiac arrest registry (20)(21)(22). We included the study with most comprehensive study database (22).…”
Section: Study Selectionmentioning
confidence: 99%
“…75 Conversely, a Korean registry-based retrospective analysis including 161 matched pairs of OHCA patients found that endovascular cooling was associated with good neurological outcomes for patients 65 or older. 76…”
Section: Confounding Factors Influencing Outcome After Ca and Ttmmentioning
confidence: 99%